Stationary And Non-Stationary Photocurrent in a Symmetric Nematic Cell with Methyl Red - Ziarmal Mawla Khan; Arian Abdul Ahad; Babazoi Basher Ahmad; Ziarmal Awal Khan (Academia Open, 2026)
General Background: Liquid crystal photovoltaics and photoelectric phenomena have garnered significant scientific interest due to their applications in optoelectronic sensing, light energy conversion, and functional soft matter systems. Specific Background: Methyl red, as an organic dye, possesses excellent visible light absorption capacity and fast photoionization characteristics, making it suitable for investigating photocurrent generation mechanisms in symmetric nematic cells. Knowledge Gap: Previous studies have either provided only qualitative descriptions of the photovoltaic effect or examined limited thickness ranges, lacking systematic exploration of how cell thickness and temperature-dependent activation processes influence photocurrent behavior in dye-doped liquid crystal systems. Aims: This study systematically investigates stationary and non-stationary photocurrents in symmetric nematic liquid crystal cells doped with methyl red across a wide range of thicknesses (1-100 μm) and temperatures. Results: The activation energy for charge carrier transport ranges from 0.05 eV to 0.87 eV across different cell thicknesses, with activation energy increasing as cell thickness decreases, while peak photocurrent values increase with decreasing thickness due to enhanced capacitance effects. Novelty: This work provides the first comprehensive quantitative analysis linking cell thickness to activation energy variations in methyl red-doped nematic systems. Implications: These findings advance understanding of charge transport mechanisms in dye-doped liquid crystals and offer critical design considerations for low-voltage optoelectronic devices, light sensors, and advanced liquid crystal-based energy conversion systems.Keywords : Photocurrent, Methyl Red, Nematic Liquid Crystal, Activation Energy, Cell ThicknessHighlight : Peak photocurrent amplitude increases with decreasing cell thickness due to enhanced capacitance effects. Activation energy ranges from 0.05 eV to 0.87 eV, rising as layer thickness decreases. Light absorption in thicker nematic layers increases steady-state current through reduced grounded electrode transmission.